Review Of The Maritime Tourism Development Model In The Anambas Islands Through A Digital Approach - Mohammad Taufik; I Ketut Gunawan; Etika Khairina; Galih Arief Imawanto (Journal of Governance and Public Policy, 2024)
This research aims to build an understanding of the currently developing academic literature on marine tourism in the Anambas Islands as one of the potential areas. Maritime tourism can be developed from a digital and institutional development policy perspective, considering that the impact of tourism through maritime tourism is so broad/multiplier effect, including trade connectivity and communication between nations, so that it becomes one way to maintain maritime affairs. This study used a qualitative method. Data sources are obtained from primary and secondary data. Data collection techniques involved observation, interviews, documentation, FGD, and triangulation, while N-Vivo12 Plus assisted data analysis techniques. The research results showed that the Anambas Regency Government has not fully implemented digital-based development. There have been no regulations governing the development of digital-based marine tourism, both in strategic plans and SOPs in regulations that do not specifically address development. Second, digital media in developing marine tourism is not optimal; there is a lack of social media platforms to raise and attract public attention. The branding carried out is only limited to providing information about tourist attractions, displaying attractive photos, and at least creating marketing campaigns such as events held on the Anambas Islands, and minimally discussing access to the Anambas Islands so that tourists feel that the distance is far away and are reluctant to visit them. Overall, digital-based development is limited to uploading on social media, even though the understanding of digital-based development is broader and far from just sharing on social media. The government should have the ability to innovate and adapt in the face of various changes, such as preparing development plans based on various information on transportation access telecommunications, which can provide complete information to potential visitors so that they can have a variety of experiences.